Comprehensive Clinical and Pathological Analysis of Chondroblastic Osteosarcoma Masquerading as an Aneurysmal Bone Cyst in an Adolescent Patient: A Multidisciplinary Diagnostic Journey - Belinda Azhari Siswanto; Bima Mahardika Aji; Istan I. Irsan; Satria P. Persada Isma; Dandy D. Adiwignyo; Eviana Norahmawati (Jurnal Locus Penelitian dan Pengabdian, 2026)
Osteosarcoma is the most common primary malignant bone tumor, primarily affecting adolescents and young adults during periods of rapid skeletal growth. Chondroblastic osteosarcoma (COS) is a histological variant that poses a diagnostic challenge due to its extensive cartilaginous matrix, which can obscure the critical diagnostic feature: malignant osteoid production. This diagnostic complexity is further exacerbated when the tumor exhibits secondary aneurysmal bone cyst (ABC) changes, often leading to an initial misdiagnosis as a benign lesion. To analyze a case of chondroblastic osteosarcoma with secondary ABC changes, highlighting the importance of a multidisciplinary approach in diagnosing and managing high-grade bone tumors in adolescent patients. A case study of a 17-year-old male presenting with progressive pain and swelling in the right thigh. Diagnosis was confirmed through incisional biopsy, immunohistochemical profiling (positive for SATB2, P53, S100, and Osteocalcin), and MRI findings, which initially suggested an ABC. MRI findings indicated an aggressive bone tumor with fluid-fluid levels characteristic of ABC. However, after biopsy and immunohistochemical analysis, the final diagnosis was confirmed as high-grade chondroblastic osteosarcoma with secondary ABC changes. The patient underwent neoadjuvant MAP chemotherapy and limb-salvage surgery. This case underscores the importance of maintaining a high index of suspicion for malignancy in adolescent patients presenting with cystic bone lesions. A multidisciplinary approach involving clinical, radiological, and pathological correlation is crucial to prevent diagnostic delays and ensure the initiation of appropriate high-grade sarcoma therapy.